Vegetation Cover Stratification of Different Land Uses on Loess Plateau - Lyu Du; Zhang Xiaoping; Liu Baoyuan; He Liang; He Jie (Shuitu baochi tongbao, 2022)
[Objective] The vegetation cover of the Loess Plateau under different land uses was analyzed in order to provide data support for monitoring the changes of vegetation cover in the region, especially non-photosynthetic (fNPV) vegetation cover, and provide a reliable basis for the application of remote sensing estimation of vegetation cover in soil erosion prediction. [Methods] Seven vegetation sample plots under different land use types on the Loess Plateau were selected. A stratified vegetation cover survey was carried out at half-month intervals by the sample band method. Then the intra-annual changes of fPV (photosynthetic vegetation) and fNPV for different vegetation types and layers were analyzed, thereby providing data support for acquiring vegetation factors for an erosion process model. [Results] ① The total projected cover of the six communities (i.e., sand land, grassland, artificial Caragana korshinskii forest, artificial Pinus tabuliformis. forest, and two natural forests at Huangling and Qinling area) did not vary significantly during the year. Both the projected fPV and its proportion to total projected cover increased gradually over time and reached maximum values in July to September, and then decreased rapidly after September. However, the projected fNPV showed the opposite change over time than observed for projected fPV. The projected fPV and fNPV of agricultural land varied dramatically within a year because of the influence of tillage factors. ② During July to September, the proportion of projected fPV was up to 100% in Huangling and Qinling natural forests, and 60.6%, 70.5%, 58.8%, and 84.9% in the other four species, respectively. This means that only considering the projected fPV would ignore the ecological benefits of the fNPV that account for 39.4%, 29.5%, 41.2%, and 15.1% of the total cover. ③ In the vegetation types with obvious vertical structure, such as artificial C. korshinskii forest, P. tabuliformis forest, and the two natural forests in Huangling and Qinling area, the intra-annual changes of fPV and fNPV in the tree layer, bush layer, and surface layer were generally consistent with the trend of the projected fPV and fNPV, respectively. The projected total cover of the four plots was positively related to the total cover of the surface layer (R2 values up to 0.85). [Conclusion] The projection fPV and fNPV of agricultural land with different land use in Loess Plateau varied dramatically within the year, while the projection fPV increased and then decreased in other sample sites within the year, and the projection fNPV was the opposite of them. The projected fNPV, which accounted for 15.1% to 41.2% of the projected total cover, was a non-negligible ground cover component in the area. The intra-annual trends of fPV and fNPV at different layer were consistent with the projected fPV and fNPV, and there was also a significant linear correlation between the total surface cover and the projected total cover. The extraction season of FVC of agricultural land and total surface cover should be focused on during regional monitoring.